The use of Leaf Surface Contact Cues During Oviposition Explains Field Preferences in the Willow Sawfly Nematus Oligospilus - Fernandez, Patricia; Braccini, Celina Laura; Dávila, Camila; Barrozo, Romina B.; Coll Araoz, Maria Victoria; Cerrillo, Teresa; Gershenzon, Jonathan; Reichelt, Michael; Zavala, Jorge Alberto (Nature Research, 2019)
After an insect herbivore has reached its host plant, contact cues from the leaf surface often determine host acceptance. We studied contact cues during oviposition behavior of a willow pest, the sawfly Nematus oligospilus (Hymenoptera: Tenthredinidae), a specialist feeder on Salix (Salicaceae) trees, and how it determines oviposition preference in lab and field conditions. We described the sequence of behaviors that lead to egg laying on the most and least preferred willow species. Then we studied the morphology of chemosensory structures present on the female antenna, cerci and ovipositor. Since phenolic glycosides (PGs) are the main secondary metabolites present in Salicaceae species, we investigated their role in host acceptance. We quantified these compounds in different willow species and correlated PG content with oviposition preference under lab and natural field conditions. We demonstrated a major role for contact cues in triggering N. oligospilus egg laying on the leaf surface of preferred willow genotypes. Firstly cues are sensed by antennae, determining to leave or stay on the leaf. After that, sensing is performed by abdominal cerci, which finally triggers egg laying. The lack of PGs in non-preferred species and the significant correlation observed between PGs, natural damage and oviposition preference suggest a role for these compounds in host selection. Our study suggests that in specialist feeders, secondary compounds normally acting as defenses can actually act as a susceptibility factor by triggering specific insect behavior for oviposition. These defensive compounds could be selected against to increase resistance.